The Monk Encounters the Prophet—The Story of the Encounter between Monk Bahīra and Muhammad as It Is Recorded in the Syriac Manuscript of Mardin 259/2 - Bahkou, Abjar (Cultural and religious studies, 2015)
The Syriac communities have been, since the eighth century, orally circulating the story of monk Sargis-Bahīra. Although its oral tradition is widely spread, the written story is not well studied or publicized. Moreover, the oral story (stories) has been embellished and/or distorted and ends with varying conclusions. At a later period, the Christian version of Bahīra was translated into Armenian and Latin where it gained more popularity, as a means of apology. There are a few versions of the story in different languages such as Arabic, Armenian, Latin, west-Syriac and East-Syriac. It is not the purpose of this study to present a critical edition of the various versions of the story. The purpose is to present an overview that will highlight the important historical events embedded in the story and its religious motifs, with the particular attention to the Syriac manuscript of Mardin 259/2. Throughout the story, the reader will be guided to look at the text within its own historical and apologetic context.